2019
DOI: 10.1371/journal.pone.0216424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restricting movement between root and canopy populations of woolly apple aphid

Abstract: Movement of insect pests between spatially subdivided populations can allow them to recolonize areas where local extinction has occurred, increasing pest persistence. Populations of woolly apple aphid ( Eriosoma lanigerum [Hausmann]; Hemiptera: Aphididae), a worldwide pest of apple ( Malus domestica [Borkhausen]), occur both below- and aboveground. These spatially subdivided subpopulations encounter different abiotic conditions, natural enemies, and control tactics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The apparent mechanism was that as clay soils dry up, they fracture, allowing woolly apple aphids to creep underground. Mulches may have a suppressive effect comparable to sand (Orpet et al, 2019). Some commercial apple orchards employ wood chips and discovered that a 6-cm layer of manure with wood chips decreased the amount of woolly apple aphids observed in pitfall traps in apple orchards (Brown and Tworkoski, 2004).…”
Section: Mechanical Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent mechanism was that as clay soils dry up, they fracture, allowing woolly apple aphids to creep underground. Mulches may have a suppressive effect comparable to sand (Orpet et al, 2019). Some commercial apple orchards employ wood chips and discovered that a 6-cm layer of manure with wood chips decreased the amount of woolly apple aphids observed in pitfall traps in apple orchards (Brown and Tworkoski, 2004).…”
Section: Mechanical Controlmentioning
confidence: 99%
“…Provision of hay mulch around apple tree trunks significantly increased the overwintering survival rate of Aphelinus mali (Haldeman), a parasitoid of E. lanigerum . Mulches have the potential to diminish edaphic woolly apple aphid infestations in the field over time, as well as edaphic population establishment in new orchards, although they are unlikely to be a powerful control tool (Orpet et al, 2019).…”
Section: Mechanical Controlmentioning
confidence: 99%
“…Apple rootstocks, resistant to woolly apple aphid, such as 'Northern spy' (developed at East Malling Research, Kent, UK) [44], are also available, but there is little to indicate that they are widely used for this purpose [45]. At the time of writing, there were no conclusive reports of pear rootstocks that promote pest resistance.…”
Section: Varietymentioning
confidence: 99%
“…They predate on a range of pests, including aphids, midge larvae, moth larvae [89], and scale pests [90]. In cases where sticky bands were applied to the trunks of apple trees to prevent woolly apple aphid movement, researchers observed an increase in aphid colony size because the banding inadvertently prevented earwigs predating the aphid colonies [45]. A similar bioassay found that 'Tanglefoot insect exclusion bands' increased the woolly apple aphid infestation of new apple shoots by 20-25% in comparison to controls in which earwigs could access colonies [91].…”
Section: Natural Enemiesmentioning
confidence: 99%
“…Different pests are known to cause damage to different parts of plants and cause harm during different periods of the year. For example, apple aphids ( Aphis pomi ) are mainly harmful to roots or young shoots and young leaves at the upper and lower parts of the plant, whereas Oriental fruit moths (Grapholita molesta) mainly harm fruit stems and fruits and cause fruit drop . Apple leaf roller moth ( Pandemis heparana ) and apple leaf miners ( Lyonetia clerkella ) damage trees by feeding on upper young or lower mature leaves .…”
Section: Introductionmentioning
confidence: 99%